Treatment of a patient with breast cancer and glucose 6-phosphate dehydrogenase deficiency: A case report. Issue 13 (March 2019) - Chung, Wei-Pang; Hsu, Ya-Tin; Chen, Ya-Ping; Hsu, Hui-Ping
Abstract: Rationale: Glucose 6-phosphate dehydrogenase (G6PD) deficiency is the most common enzymatic disorder of red blood cells that cause hemolytic anemia. Some anticancer drugs are reported to trigger oxidative stress; however, events of hemolysis are rarely discussed in patients with G6PD deficiency required oncologic treatments. Patient concerns: Here we reported a young woman with G6PD deficiency safely undergoing breast cancer treatment. Diagnosis: A 29-year-old patient was diagnosed with advanced cancer of the right breast with tumors positive for hormone receptor and human epidermal growth factor receptor 2. Interventions: The patient received chemotherapy with doxorubicin, cyclophosphamide, and docetaxel. During the administration of docetaxel, trastuzumab was concurrently administered and was continued after the completion of docetaxel. The patient underwent adjuvant radiotherapy; meanwhile, tamoxifen was administered as adjuvant endocrine treatment. Outcomes: The treatment process was smooth. There was no evidence of hemolytic anemia. Except for hot flushes, the patient lives without remarkable side effects from ongoing or previous treatments. Lessons: Some patients have both G6PD deficiency and malignancy in a geographic area with relatively high incidence of the enzymatic disorder and certain types of cancer. We suggest that our report can contribute to the concern regarding the safety of patients with G6PD deficiency undergoing cancer treatment.